Espacios y tiempos mediados por la memoria. La toponimia en el oeste de La Pampa en el siglo XX - María Eugenia Comerci (Corpus: Archivos Virtuales de la Alteridad Americana, 2012)
Place names are the result of the meeting between spaces and times; they express a struggle for control of the territory and the construction of the collective memories. In this article we intend to analyze processes of territorialization in the west of La Pampa, establishing relationships among the categories of place, territory, toponymy, power and memory. We start from the assumption that every place, product of the process of construction of power relationships, has certain identity marks that differentiate it from others, symbolically expressed through the toponymy. Within such framework, we analyze place names, from a diachronic perspective, in four areas of the west of La Pampa. First we analyze the names given by dominant discourse and territoriality to western jurisdictions, to then address names that peasants gave to their “puestos” and their meanings. We describe and compare the names of places in the western ecoregions through case studies in the places of Chos Malal, La Humada, La Puntilla and Paso Maroma. Finally, we generate some reflections on the potential of these representations within the context of expansion of the agricultural frontier and emerging conflicts.